Measurements of diffusion coefficients in solids by means of LIBS combined with direct sectioning - Ararat Ibarguen, Carlos Eduardo (2014)
This work explore the application of Laser Induced Breakdown Spectroscopy (LIBS) to the measurement of diffusion coefficients D in solids. Different experimental set ups were tested looking for minimize the error and extend the range of D values achievable. It was found that the combination of direct sectioning with precision grinder plus LIBS is the best arrangement in order to fulfill these goals. Excellent agreement with previous results in the literature, measured with standard techniques, was obtained.